P2_10 Leap Year? Get out of Here! Part 2 - Murgatroyd, Conan; Mott, Dan; Stinton, James; Kinsman, Charlie (Physics Special Topics, 2021)
The aim of this paper was to determine by how much Earth’s rotation would have to slow down so that each orbital year was exactly 365 days, which would therefore remove the leap year. This was found to require the period of Earth’s rotation to decrease by 0.27% which corresponds to removing 1.1763E27 J of energy from the Earth. It was determined that this is not feasible because current energy production is insufficient, and also because we would have no mechanism of applying this force to the Earth even if we did meet the energy requirements.